2015
DOI: 10.2147/ijn.s83838
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and necrosis induced by novel realgar quantum dots in human endometrial cancer cells via endoplasmic reticulum stress signaling pathway

Abstract: Realgar (A S4 S 4 ) has been used in traditional medicines for malignancy, but the poor water solubility is still a major hindrance to its clinical use. Realgar quantum dots (RQDs) were therefore synthesized with improved water solubility and bioavailability. Human endometrial cancer JEC cells were exposed to various concentrations of RQDs to evaluate their anticancer effects and to explore mechanisms by the MTT assay, transmission electron microscopy (TEM), flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…A series of clinical studies and trials proved that treatment with As 2 S 2 was well tolerated, with only moderate side-effects in patients suffering from APL (13,39,40). Recent studies have also reported the potent anti-tumor properties of As 2 S 2 in various solid cancer cell lines, along with a marked reduction in cytotoxic effects in human normal cell lines (41)(42)(43). However, there have been very few studies on the anti-tumor effects of As 2 S 2 in breast cancer cells (24), and fewer studies on the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A series of clinical studies and trials proved that treatment with As 2 S 2 was well tolerated, with only moderate side-effects in patients suffering from APL (13,39,40). Recent studies have also reported the potent anti-tumor properties of As 2 S 2 in various solid cancer cell lines, along with a marked reduction in cytotoxic effects in human normal cell lines (41)(42)(43). However, there have been very few studies on the anti-tumor effects of As 2 S 2 in breast cancer cells (24), and fewer studies on the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports about ultrafine particulate matter-induced necrotic cell death have been published. 32 Necrosis induced by QDs 33,34 has also been found, while necroptosis has not been reported.…”
Section: Necrosismentioning
confidence: 99%
“…26 Similar to cadmium-containing QDs, other types of QDs have similar effects on apoptosis. 34,35 It was generally acknowledged that apoptosis usually takes place through mitochondrial or death receptor pathway with respective activation of caspase 9 and caspase 8. Initiation of extrinsic pathway by stimulation of QDs was attributed to release of tumor necrosis factor-α or contact of Fas ligand with Fas receptor.…”
Section: Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Ki-67, a nuclear protein, is widely used as a tumour proliferation marker. Our study showed that the A previous study showed that cell apoptosis may be induced by ER stress and mitochondrial membrane permeability [27,28]. CHOP, a key protein of ER stress-mediated cell death, also known as a bZIPcontaining transcription factor, targets many apoptotic genes, including NOXA, modifying their expression and ultimately resulting in apoptosis [29].…”
Section: Discussionmentioning
confidence: 53%